Comparison of "the decoy effect" and "multiple equivalent simultaneous offers" as negotiation strategies - Gotvan, Lana K. (Podjetje in delo, 2023)
This article presents and compares two negotiation strategies. Section 1 introduces the article. In Section 2, this article explains the concept of "the decoy effect", which is then assessed as a negotiation strategy. In Section 3 of the article, I introduce and assess the concept of "multiple equivalent simultaneous offers" (hereinafter, "MESOs") and draw relevant comparisons to the decoy effect. In Section 4, the article compares the two negotiation strategies in more detail, analysing the Negotiator's Dilemma and other related issues. This article submits that both the use of MESOs and the use of the decoy effect are effective strategies in integrative negotiations and contain both value-claiming and value-creating elements. Negotiators often rely on cognitive shortcuts, thus violating the assumption of rationality that underpins classical economic theory. Hence, negotiators can facilitate negotiations by exploiting cognitive biases that cause predictable "errors" in human decision-making. Through mastering negotiation strategies such as the decoy effect and MESOs, the negotiating parties can deal with conflict more effectively, improve their relationship, claim more value in negotiations, and reach (Pareto) optimal agreements.
Keywords: ekonomija; pogajalske strategije; pogajanja; sočasne ponudbe; učinek vabe; vedenjska ekonomija